Understanding Pursuing as an Entrepreneurial Competence and the Relationship with Performance of Value-system Actors in Kenya’s Leather Industry - KAMURI, SIMON (Machakos University Press, 2021)
Entrepreneurship and associated behavioural competencies continue to be important but insufficiently studied phenomena, especially in African factor-based industries such as leather, and from an ecosystem perspective. Further, entrepreneurial orientations and competencies have not been adequately distinguished nor understood in past studies. By adapting an empirically validated construct of pursuing as an entrepreneurial competence measure, this study investigated the behaviour in determining firm-level performance of industry actors. A sample of players from Kenya’s leather industry were studied representative of an entrepreneurial ecosystem. SPSS was used for exploratory and inferential analysis to establish the validity of the constructs and their hypothesized relationship. Pursuing competences of managers as key-informants of Kenya’s leather industry business organizations were measured and tested for determination of expected performance outcomes. Mixed sampling of sixty-eight Leather Articles Entrepreneurs Association (LAEA) members and the associated value-system actors were studied, with a response rate of 76%. Factor analysis showed pursuing and performance were uni-dimensional entrepreneurship constructs comprising three and nine indicators respectively. Inferential analysis showed that pursuing determined performance of industry value-system actors. This study affirmed earlier research the validity of pursuing as an entrepreneurial competence construct and its determination of firm-level performance. The study therefore contributes to a new perspective of the dimensions of entrepreneurial competence and growing scholarship in industry ecosystems. Development of pursuing as an entrepreneurial competence of key decision makers in industry ecosystems can positively impact business performance. The study recommends that scholarship, policies and individual development programs in entrepreneurship should adopt pursuing as a valid dimension of entrepreneurship behaviour.
Keywords: Pursuing; Entrepreneurial competence; Performance; Value-system actors; Leather industry; Entrepreneurial ecosystems